Bony impressions on caput and neck of human femora in Indian Population. - Ghosh S,; Sethi M,; Vasudeva N, (Department of Surgery, UKM Medical Centre, 2014)
Idiopathic osteoarthritis of the hip has been currently attributed by researchers to the repetitive microtrauma caused to the femoral neck by its impingement against the acetabular rim. This impingement occurs as a result of abnormal morphological traits like Allen’s fossa, Poirier’s Facet, and Posterior Cervical Imprint that appear on the proximal end of femur especially on the neck. Hence, this study was undertaken to investigate the incidence of these traits in the Indian population and to find a correlation between the occurrence of the trait and the side and sex of the bone. The study was conducted on 152 adult dried femora in the Department of Anatomy, Maulana Azad Medical College, New Delhi, India. The positive findings were photographed. The significance of the correlation was found out using Chi-square test. Allen’s Fossa was found to occur in 71.1% of the total bones assessed Poirier’s Facet in 31.6% and Posterior Cervical Imprint in 19.7%. Out of these, a significant side association was found for the Poirier’s Facet with a predominance of the left side. All the traits were found to be more in males with a significant sex variation for Poirier’s Facet. Each trait demonstrated a significant side and gender dimorphism.